2020
DOI: 10.1136/bjophthalmol-2019-315394
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of diabetic retinopathy grading by an artificial intelligence-enabled algorithm compared with a human standard for wide-field true-colour confocal scanning and standard digital retinal images

Abstract: BackgroundPhotographic diabetic retinopathy screening requires labour-intensive grading of retinal images by humans. Automated retinal image analysis software (ARIAS) could provide an alternative to human grading. We compare the performance of an ARIAS using true-colour, wide-field confocal scanning images and standard fundus images in the English National Diabetic Eye Screening Programme (NDESP) against human grading.MethodsCross-sectional study with consecutive recruitment of patients attending annual diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Testing the data collected from three nations with variation of these factors showed that, as long as the quality assessment is in place in the workflow, the performance of the algorithm is consistent. This is in line with other studies, 29 , 30 where AI was evaluated in coordination with either assessing the quality and protocol adherence of images, or data imaged with mydriasis through a high-quality imaging platform.…”
Section: Discussionsupporting
confidence: 83%
“…Testing the data collected from three nations with variation of these factors showed that, as long as the quality assessment is in place in the workflow, the performance of the algorithm is consistent. This is in line with other studies, 29 , 30 where AI was evaluated in coordination with either assessing the quality and protocol adherence of images, or data imaged with mydriasis through a high-quality imaging platform.…”
Section: Discussionsupporting
confidence: 83%
“…Only a study by Olvera-Barrios and coauthors reported a similar sensitivity for detecting DR (92%), compared with human graders using the commercially available AI algorithm EyeArt (version 2.1.0; Eyenuk, Inc., Woodland Hills, CA). 25 In contrast, our study used separate models for Nidek and Eidon due to the poor diagnostic accuracy achieved when using the same DR screening model. The difference in the model accuracies of the two fundus cameras might result from differences in the color, image resolution, field of view, and lesion characteristics observable in their respective images.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, there has been a lot of research on artificial intelligence (AI) using fundus photographs, OCT, and OCT angiography images [36][37][38][39][40], and there is a highly likelihood that color SLO, which has high image quality with a large amount of information, will be useful for this kind of automatic diagnosis by AI. Indeed, preliminary studies using AI and color SLO have been reported [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…[14]. In addition, a confocal light-emitting diode-based retinal imaging system (Eidon, Centervue, Padova, Italy), which is a similar concept with the color SLO, was also launched [15,16].…”
Section: Recent Advances Of Color Slomentioning
confidence: 99%